Crash course in basic cataloging with RDA - Moulaison, Heather Lea; Wiechert, Raegan (Santa Barbara Libraries unlimited, 2015)
"Covering tools, terminology, and the FRBR-based RDA approach to description, this book explains the current principles of organization of information and basic cataloging practices for non-catalogers, enabling readers to understand elements of the cataloging process and interact with records in a basic manner"--
Machine generated contents note: Chapter 1: What is Cataloging? -- Chapter 2: ILSs and the Online Library Catalog -- Chapter 3: Materials and Approaches in Library Cataloging -- Chapter 4: Encoding RDA Cataloging Records -- Chapter 5: RDA, the Toolkit, and Works and Expressions -- Chapter 6: RDA: Manifestations and Items -- Chapter 7: Access Points and Controlled Vocabulary -- Chapter 8: Subject Access and Controlled Vocabulary -- Chapter 9: Classification -- Chapter 10: Working with Catalog Records and Materials -- Appendix A: Examples of RDA Cataloging Records in MARC -- Appendix B: Cataloging Tools: A Bibliography/Webliography -- Appendix C: Professional Resources for Catalogers -- Index .
Includes bibliographical references and index.
Keywords: Resource description & access; Cataloging; Classification -- Books; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General; LANGUAGE ARTS & DISCIPLINES / Study & Teaching